Development of Human Values-Based Textbook Patterns of Al-Qur'an Reading at Pesantren Yogyakarta - Munjahid, Munjahid (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The research aimed to discover and describe the urgent textbook pattern for reading al-Qur'an at Al-Fataa Islamic Boarding School before treatment and the textbooks needed for treatment, the ability to read al-Qur'an, and the humanist attitude of students before and after treatment. This research type was research and development with a qualitative descriptive approach. We collected data using observation, interviews, documentation, testing, and questionnaires. The research showed that the textbook pattern before treatment was much less coherent subject matter, the separation between theory and practice, and the psychomotor aspects were more dominant. The student's ability after treatment: All students passed; 17 got a B, and 9 got an A. Students who were able to read al-Qur'an without tajwīd required 12 meetings, and students were able to read al-Qur'an according to the science of recitation, and garīb Al-Qur'an takes 78 hours. The humanist attitude of the students after the treatment was all development models were perfect. The Self-Concept model was perfect except for two students who had good predicate. Model Sensitivity and group orientation were all excellent. The consciousness-expansion model was mostly better.